Biogenesis of circRBM33 mediated by N6-methyladenosine and its function in abdominal aortic aneurysm - Yingqi Xu; Xiang Weng; Jiacong Qiu; Shizhi Wang (Epigenetics)
This study aimed to explore whether m6A modification affects the biogenesis of circRBM33, which is involved in the progression of abdominal aortic aneurysm (AAA). For in vitro experiments, vascular smooth muscle cells (VSMCs) were treated with Ang II. MeRIP‒PCR was used to assess m6A modification of circRBM33. Gene expression was measured using RT‒qPCR and Western blotting. For in vivo experiments, a mouse model of AAA was established via Ang II infusion. HE, Sirius Red and TUNEL staining was performed to evaluate pathological changes and cell apoptosis in aortic vessels. The results showed that the m6A level of circRBM33 was abnormally increased in Ang II-induced VSMCs. In addition, METTL3 positively regulated circRBM33 expression. YTHDC1 deficiency decreased circRBM33 expression but had no effect on RBM33 mRNA expression. Notably, neither METTL3 nor YTHDC1 influenced the stability of circRBM33 or RBM33 mRNA. The interaction between circRBM33 and METTL3/YTHDC1 was verified by RIP analysis. Moreover, the Ang II-induced increase in circRBM33 expression was reversed by cycloleucine (an inhibitor of m6A methylation). Importantly, the m6A modification and expression of circRBM33 in the circRBM33-m6A-mut2-expressing VSMCs were not altered by METTL3 silencing. Mechanistically, METTL3/YTHDC1 modulates the biogenesis of circRBM33 in an m6A-dependent manner. In addition, circRBM33 knockdown alleviated AAA by reducing ECM degradation in the Ang II-infused mice. In conclusion, this study demonstrated that METTL3/YTHDC1-mediated m6A modification modulates the biogenesis of circRBM33 from exons of the RBM33 gene. Moreover, knockdown of circRBM33 alleviated AAA by reducing ECM degradation, which may provide a novel therapeutic strategy for treating AAA.